The effect of milling time on Ni0.5Zn0.5Fe2O4 compositional evolution and particle size distribution - Ismail, Ismayadi; Hashim, Mansor; Matori, Khamirul Amin; Alias, Rosidah (Science Publications, 2009)
Problem statement: This study involved an investigation to ascertain the diffusion of NiO and ZnO into the tetrahedral and octahedral sites using mechanical alloying method. The effect of mechanical alloying towards particle size was also reported.